A case study of computerisation in the banking industry - automating the accounting system of united overseas banking group - Goh, Sia (2014)
Many final year projects in the past have done many case studies of companies and provided the solutions for the corporations. We feel that with the limited knowledge and experience of undergraduates, the solutions provided may not be practical to the corporations. As such, we will, in this project, conduct a case study whereby we will objectively evaluate the feasibility of a new accounting system as implemented by a major corporation. In this way, the solution- being the new accounting system- will be provided by the organisation itself. Therefore, instead of providing solutions to corporate problems, we will study the existing problems and determine if the solutions provided by the corporation indeed address these problems. In this way, it will enable us, the students, to better comprehend how the professionals handle corporate problems and how systematically changes are implemented. We will also be reviewing the anticipated problems as brought about by the new system In due course, these will be discussed with the management as an additional feedback to the new system.